Anti-Money Laundering and Combating the Financing of Terrorism : Observations from the Work Program and Implications Going Forward. (Policy Papers; Policy Paper ;, 2005)
This paper provides a summary of the IMF and the World Bank work programs on anti-money laundering and combating the financing of terrorism following the Fund and Bank Boards' decisions in March 2004 to endorse the revised FATF standard (2003 version) and methodology for the purposes of preparing ROSCs and to expand the areas of Bank/Fund responsibility to cover the revised FATF standard comprehensively. It draws lessons on what has worked well and the challenges and discusses the work program going forward.